ORIENTASI BANGUNAN RUMAH SUSUN MENUJU HUNIAN VERTIKAL YANG EFISIEN ENERGI Studi Kasus Blok A dan B, Rumah Susun Kudu Semarang - Firmandhani, Satriya Wahyu; Pandelaki, Edward Endrianto (MODUL, 2020)
This research responded to environmental issues that arise related to green design as the responsibility of architectural actors. A building is now required to have environmentally friendly values, one of that can be reflected in the energy efficiency of the building. Kudu Flats is one of the towers in the city of Semarang which had several blocks with different orientations. Related to these environmental issues, this study aimed to determine the level of energy efficiency in the Kudu flats with consideration of building orientation, openings and shading devices using quantitative methods based on edge design. This study revealed that flats blocks that have smaller openings in the east-west direction are more energy efficient and rotating the building orientation 15 Â° from the wind direction will make the building more energy efficient.